Learning in socio-spatial context: an individual perspective. (1st March 2014) - Rutten, Roel
Abstract : Roel Rutten is assistant professor at the School of Social and Behavioural Sciences of Tilburg University and has worked as a consultant of regional innovation policy. His research interests include innovation and organization and the geography of innovation and learning. He is a founding member of the Social Dynamics of Innovation Networks research community and an active member of the Regional Studies Association. He frequently engages with practitioners in the field of innovation and regional development.